Foreign Language Learning: A Study of Digital Literacy in Generation Z - Pikri, Faizal; Rahayu, Kartini; Muhammad Idrus Hamid B, La Ode; Abdullah, Dahlan (Yayasan Pendidikan Islam Daarut Thufulah, 2023)
Background. The background of this research lies in the change in educational paradigm triggered by the use of technology in foreign language learning. Technology integration has great potential to increase students' engagement, motivation and understanding of the target language. Along with this, Generation Z, as a group of students who grew up in the era of digital technology, has become the object of study because of the tendency to use technology intensively in learning. Purpose. This research has the general aim of exploring and understanding how digital literacy can be optimized in foreign language learning in Generation Z. Specifically, this research aims to identify patterns of technology use, detail the obstacles faced, and design solutions that can be implemented in increasing the digital literacy of students majoring in foreign languages. Method. This research methodology carries a quantitative approach with a research design in the form of a survey. The use of questionnaires as research instruments was carefully designed to explore aspects of digital literacy. Data collection was carried out via the Google Form platform with the participation of 30 Generation Z students, which is expected to provide an in-depth perspective regarding the experiences and challenges in their digital literacy. Results. The results of data analysis show a significant level of involvement of students in the use of digital devices, with the majority choosing learning via an application or digital platform. Digital literacy is an important focus, and the majority of students feel comfortable and confident in using digital resources. Nonetheless, challenges such as confusion in evaluating the authenticity of online information need to be addressed. Conclusion. Results Barriers and challenges to digital literacy include accessibility inequalities, lack of training, and technological changes. Strategies to overcome these obstacles vary, with students more likely to seek help from friends or teachers, seek online guidance, and try new learning methods. In conclusion, this research makes a significant contribution to the understanding of digital literacy of students majoring in foreign languages, with an emphasis on learning strategies that are holistic and tailored to students' individual preferences and needs.